The orthodontic periodontal interface: A narrative review - Gurkeerat Singh; Puneet Batra (Wolters Kluwer Medknow Publications, 2014)
The purpose of this review is to highlight the orthodontics and periodontics interface in clinical practice for optimized treatment outcomes. Orthodontic treatment aims at providing an acceptable functional and esthetic occlusion. Tooth movements are strongly related to interactions of teeth with their supportive periodontal tissues. In recent years, due to the increased number of adult patients seeking orthodontic treatment, orthodontists frequently face patients with periodontal problems.Esthetic considerations, like uneven gingival margins or functional problems resulting from inflammatory periodontal diseases, should be considered in orthodontic treatment planning. Potentials and limitations that derive from the interdisciplinary approach of complex orthodontic-periodontal clinical problems are discussed along with the role of light forces and self-ligating brackets.